Comparison of Hounsfield Units within the Humeral Trochlea and Medial Coronoid Process in a Population of Labrador X Golden Retriever Guide Dogs and Border Collies - Ellis, Luke F.; House, Arthur K.; Shimura, Kiyoko; Frances, Mika (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to determine if variations in Hounsfield units (HU) are present within the elbow between asymptomatic dogs of two breeds of dogs susceptible to elbow dysplasia.Study Design Guide Dogs and Border Collies that presented for routine computed tomography (CT) screening for elbow dysplasia prior to breeding were evaluated. All dogs had no documented history of lameness. Dogs diagnosed with CT as being free of elbow dysplasia were included. The CT images were randomized and assessed by three blinded observers. A standardised approach to CT image reconstruction to create consistent image planes was used. Hounsfield units were measured within a standardised region of interest (ROI) at the humeral trochlea and medial coronoid process. The minimum, mean and maximum HU within each ROI was recorded.Results Eighty-six elbows were included in the study with 32 Guide Dogs, and 11 Border Collies. Guide Dogs had significantly higher minimum (99.75 HU, 95% confidence interval [CI]: 15.02–184.48, p = 0.022), mean (115.09 HU, 95% CI: 80.53–149.64, p < 0.01) and maximum (74.00 HU, 95% CI: 44.58–103.42, p < 0.01) difference in HU within the medial coronoid process ROI, and significantly higher mean (146.49 HU, 95% CI: 100.12–192.87, p < 0.01) and maximum (147.77 HU, 95% CI: 102.57–192.97, p < 0.01) difference in HU within the humeral trochlea ROI.Conclusion In this dataset breed variations in elbow HU were present between asymptomatic Guide Dogs and Border Collies. This needs to be considered in breeding screening programmes to avoid over-interpretation of elbow sclerosis, in the absence of elbow pathology.
Keywords: canine elbow dysplasia; Hounsfield units; computed tomography; medial coronoid process; humeral trochlea